Room‐Temperature Negative Differential Resistance and High Tunneling Current Density in GeSn Esaki Diodes. Issue 41 (13th September 2022) - Liu, Chia‐You; Tien, Kai‐Ying; Chiu, Po‐Yuan; Wu, Yu‐Jui; Chuang, Yen; Kao, Hsiang‐Shun; Li, Jiun‐Yun
Abstract: Tunnel field‐effect transistors (TFETs) are a promising candidate for low‐power applications owing to their steep subthreshold swing of sub‐60 mV per decade. For silicon‐ or germanium‐based TFETs, the drive current is low due to the indirect band‐to‐band tunneling (BTBT) process. Direct‐bandgap germanium–tin (GeSn) can boost the TFET performance since phonon participation is not required during the tunneling process. Esaki diodes with negative differential resistance (NDR) are used to characterize the BTBT properties and calibrate the tunneling rates for TFET applications. This work demonstrates high‐performance GeSn Esaki diodes with clear NDR at room temperature with very high peak‐to‐valley current ratios of 15–53 from 300 K to 4 K. A record‐high peak current density of 545 kA cm −2 at 4 K is also reported for the tensile‐strained Ge0.925 Sn0.075 device (strain ≈0.6 %). By applying tensile stresses to n‐GeSn epitaxial films, the direct BTBT process dominates, leading to high tunneling rates. Hall measurements further confirm that more electrons populate in the direct Γ valley in the tensile‐strained n‐GeSn epitaxial films. Abstract : Negative differential resistance (NDR) in GeSn Esaki diodes at room temperature with very high peak‐to‐valley current ratios is reported. By applying tensile stresses on GeSn epitaxial films, a record‐high tunneling current density of 0.5 MA cm −2 is achieved among all group‐IV Esaki diodes since phonon participation is no longer required in direct‐bandgap germanium–tin.